Initial results of a study into the estimation of the development of frequency lock-in for offshore structures subjected to ice loading - Hendrikse, H. (author); Seidel, Marc (author); Metrikine, A. (author); Loset, Sveinung (author) (2017)
Ice-induced vibrations have to be considered in design of vertically sided offshore structures subjected to loading by sea ice, such as offshore wind turbines and oil- and gas platforms. The interaction between ice and structure may result in high global peak loads and the occurring structural vibrations can contribute significantly to the overall fatigue of the structure. A regime of particular interest is the frequency lock-in regime in which the interaction causes the structure to oscillate at high amplitude with a frequency close to one of its natural frequencies. Assessment of frequency lock-in in the design phase can be done based on simple approaches once for given ice conditions the natural modes to experience frequency lock-in and the range of ice drift velocities for which lock-in develops are known. Determining those modes and velocities is however challenging due to the nonlinear nature of the interaction between ice and structure and limited available reference data. In this paper two methods are applied to determine the structural modes and ice drift velocities required as an input for simplified design approaches. The first method is the application of design standards and estimation formulas available from literature. The second method is the application of a recently developed numerical model for simulation of the interaction. The methods are applied to two existing structures which have experienced frequency lock-in and an offshore wind turbine designed to be employed at a location with mild ice conditions. Results show that the estimation formulas do not match with full-scale observations of the existing structures and can therefore not be applied to obtain input for the simplified design approaches. The second method shows to give simulation results consistent with the full-scale observations. Application to the offshore wind turbine reveals that it is most susceptible to frequency lock-in in the second mode. Offshore Engineering Applied Mechanics